KLASIFIKASI TANAH DESA TARO, KECAMATAN TEGALLALANG KABUPATEN GIANYAR BERDASARKAN SISTEM TAKSONOMI TANAH (SOIL CLASSIFICATION OF TARO VILLAGE, TEGALLALANG DISTRICT, GIANYAR REGENCY) - KUSMIYARTI, TATI BUDI; BAYU AJI, HIMAWAN; BHAYUNAGIRI, IDA BAGUS PUTU (AGRITROP, 2010)
The purpose of the research was to classify of soil on Taro Village, Tegallalang District, Gianyar Regency. Soil survey methods and analysis in laboratory were used in this research. Some parameters of soil properties were observed: soil morphology in the field, and physical, chemical and mineralogical soil properties in the laboratory. Soil classification based on Soil Taxonomy System by using Keys to Soil Taxonomy (2003). There are four families in Taro village, namely: (1) Ruptic-Alfic Dystrudepts, coarse loamy, mixed, isothermic; (2) Aeric Epiaquepts, coarse loamy, mixed, isothermic; (3) Humic Eutrudepts, coarse loamy, mixed, isothermic; (4) Typic Eutrudepts, coarse loamy, mixed, isothermic.